Assessing the predictive ability of sovereign default risk on exchange rate returns. (March 2018) - Foroni, Claudia; Ravazzolo, Francesco; Sadaba, Barbara
Highlights: Identify new source of currency markets risk premia: expected sovereign default risk. Expected sovereign default risk can explain future exchange rate movements. For most economies the default risk model improves the RW model forecasting accuracy. Strong evidence of predictability is found for developed economies at daily frequency. Our model forecasting gains over time coincide with important domestic/global events. Abstract: Increased sovereign credit risk is often associated with sharp currency movements. Therefore, expectations of the probability of a sovereign default event can convey important information regarding future movements of exchange rates. In this paper, we investigate the possible pass-through of risk in the sovereign debt markets to currency markets by proposing a new risk premium factor for predicting exchange rate returns based on sovereign default risk. We compute it from the term structure at different maturities of sovereign credit default swaps and conduct an out-of-sample forecasting exercise to test whether we can improve upon the benchmark random walk model. Our results show that the inclusion of the default risk factor improves the forecasting accuracy upon the random walk model and alternative models provide less accurate predictions.